Bioinspired Membrane-Coated Nanoplatform for Targeted Tumor Immunotherapy - Mu, Dan; He, Pan; Shi, Yesi; Jiang, Lai; Liu, Gang (Frontiers in Oncology, 2022)
Immunotherapy can effectively activate the immune system and reshape the tumor immune microenvironment, which has been an alternative method in cancer therapy besides surgery, radiotherapy and, chemotherapy. However, the current clinical outcomes are not satisfied due to the lack of targeting of the treatment with some unexpected damages to the human body. Recently, cell membrane-based bioinspired nanoparticles for tumor immunotherapy have attracted much attention because of their superior immune regulating, drug delivery, excellent tumor targeting and biocompatibility. Together, the article reviews the recent progress of cell membrane-based bioinspired nanoparticles for immunotherapy in cancer treatment. We also evaluate the prospect of bioinspired nanoparticles in immunotherapy for cancer. This strategy may open up new research directions for cancer therapy.